A New Approach for Sintering Simulation of Irregularly Shaped Powder Particles—Part II: Statistical Powder Modeling. Issue 8 (1st June 2022) - Weiner, Max; Zienert, Tilo; Schmidtchen, Matthias; Hubálková, Jana; Aneziris, Christos G.; Prahl, Ulrich
Abstract : Current simulations of sintering processes work often with heavily idealized powder geometries. As sintering is mainly driven by gradients of chemical potential due to surface curvatures, a realistic description of the particle geometry is essential for achieving precise simulation results. In previous work, a model able to simulate sintering behavior of irregularly shaped particles was shown. Herein, a statistical approach for description of particles' morphology in a powder mixture is developed by fitting a simplified particle shape model on image data. The obtained data are analyzed and conditioned for input into sintering simulation. Instead of building an equivalent volume cell of particles, as common, a Monte Carlo approach is applied to describe the sintering behavior of the powder. The resulting distributions of sintering time curves are analyzed regarding the influence of the morphology description in comparison to circular particles. Using thumb rules of Cohen's effect size, a small effect on shrinkage and a medium effect on neck radii is observed. Abstract : Current sintering models often work with spherical particles geometries. However, diffusion and alongside sintering progress are driven mainly by gradients of chemical potential due to surface curvatures. Therefore, the description of particles geometry heavily influences sintering simulation results. In this work, Part II, a sintering model for nonspherical particles is developed and evaluated.